A Case Study of Brass Foundry Workers' Estimated Lead (Pb) Body Burden from Different Exposure Routes. Issue 9 (22nd June 2020) - Julander, Anneli; Midander, Klara; Garcia-Garcia, Sandra; Vihlborg, Per; Graff, Pål
Abstract: Objectives: The most pronounced occupational exposure routes for lead (Pb) are inhalation and gastrointestinal uptake mainly through hand-to-mouth behaviour. Skin absorption has been demonstrated for organic Pb compounds, but less is known about inorganic Pb species. Several legislative bodies in Europe are currently proposing lowering biological exposure limit values and air exposure limits due to new evidence on cardiovascular effects at very low blood Pb levels. In light of this, all exposure routes in occupational settings should be revisited to evaluate how to lower the overall exposure to Pb. Methods: The aim of the study was to investigate the possible exposure routes in workers operating computer numerical control-machines in a brass foundry and specifically to understand if metal cutting fluids (MCFs) used by the workers could lead to skin absorption of Pb. The different bronze alloys at the facility may contain up to 20% Pb. After obtaining written informed consent from the workers ( n = 7), blood, skin wipes, and personal air samples were collected. In addition, MCFs used on the day of exposure measurements were collected for in vitro skin absorption studies using stillborn piglet skin mounted in static Franz diffusion cells ( n = 48). All samples were analysed for Pb content using inductively coupled plasma mass spectrometry. Results: Pb air concentration (<0.1–3.4 µg m −3 ) was well below the Swedish occupational exposure limit value. Blood Pb was in the range of <0.72–33 µg dl −1, and Pb on skin surfaces, after performing normal work tasks during 2 h, was in the range of 0.2–48 µg cm −2 . Using the MCFs in diffusion cells showed that skin absorption had occurred at very low doses, and that up to 10% of the Pb content was present in the skin after 24 h exposure. Using these results in the US EPA adult lead model, we could estimate a contribution to blood Pb from the three exposure routes; where hand-to-mouth behaviour yielded the highest contribution (16 µg Pb dl −1 blood), followed by skin absorption (3.3–6.3 µg Pb dl −1 blood) and inhalation (2.0 µg Pb dl −1 blood). Conclusions: This case study shows that MCF may lead to skin absorption of inorganic Pb and contribute to a systemic dose (quasi-steady state). Furthermore, even though good hand hygienic measures were in place, the workers' skin exposure to Pb is in all likelihood an important contributor in elevating blood Pb levels. Skin exposure should thus be monitored routinely in workers at facilities handling Pb, to help reducing unnecessary occupational exposure.